2016
DOI: 10.3390/c2030020
|View full text |Cite
|
Sign up to set email alerts
|

Simple Process for Sidewall Modification of Multi-Walled Carbon Nanotubes with Polymer Side Chain Radicals Generated by Ultraviolet-Induced C–Cl Bond Dissociation of Polystyrene Derivatives

Abstract: Abstract:In this work, we investigated a simple one-step process for the formation of chemical bonds between multi-walled carbon nanotubes (MWCNTs) and benzyl-type side chain radicals generated by UV photolysis of polystyrene derivatives containing the chloromethyl (-CH 2 Cl) group. Poly(4-chloromethyl)styrene, or styrene/4-(chloromethyl)styrene random copolymer, was mixed with MWCNTs in 1-methyl-2-pyrrolidone and irradiated with ultraviolet (UV) light. Films of polymer/MWCNT mixtures before and after UV irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The Raman spectra of PC and PC-SBMA-24 (Figure A) show two prominent peaks, the D and G bands at 1581 and 1349 cm –1 , respectively. It is universally acknowledged that the G band is due to the in-plane vibration of the sp 2 carbon atoms, whereas the D band is a defect-induced Raman feature representing the imperfect crystalline structure of the material. , The ratio of the intensities ( I G / I D ) is a measure of the degree of structural disorder. Compared with pristine PC, the G/D ratio calculated for PC-SBMA-24 decreased considerably from 1.08 to 0.88, indicating that the carbon surface defects increased with the grafting of PSBMA zwitterionic polymer brushes through SI-ATRP modification. The I G / I D of PC-PDA and PC-Br also decreased to 0.97 and 0.92 (Figure S6), respectively, which may be caused by the successful coating with PDA and immobilization of the ATRP initiator.…”
Section: Resultsmentioning
confidence: 99%
“…The Raman spectra of PC and PC-SBMA-24 (Figure A) show two prominent peaks, the D and G bands at 1581 and 1349 cm –1 , respectively. It is universally acknowledged that the G band is due to the in-plane vibration of the sp 2 carbon atoms, whereas the D band is a defect-induced Raman feature representing the imperfect crystalline structure of the material. , The ratio of the intensities ( I G / I D ) is a measure of the degree of structural disorder. Compared with pristine PC, the G/D ratio calculated for PC-SBMA-24 decreased considerably from 1.08 to 0.88, indicating that the carbon surface defects increased with the grafting of PSBMA zwitterionic polymer brushes through SI-ATRP modification. The I G / I D of PC-PDA and PC-Br also decreased to 0.97 and 0.92 (Figure S6), respectively, which may be caused by the successful coating with PDA and immobilization of the ATRP initiator.…”
Section: Resultsmentioning
confidence: 99%
“…The bond formation process is depicted in Scheme 1. Recently, we reported the photoinduced chemical bond formation between CNTs and poly(pchloromethyl)styrene [23]. We found that the C-Cl bonds of the chloromethyl side chains (-CH2Cl) of the polymer dissociated with ultraviolet (UV) irradiation to form benzyl-type side chain radicals.…”
Section: Introductionmentioning
confidence: 99%